SIM-XL: A powerful and user-friendly tool for peptide cross-linking analysis - Lima, Diogo B.; Lima, Tatiani B. de; Balbuena, Tiago S. [UNESP]; Neves-Ferreira, Ana Gisele C.; Barbosa, Valmir C.; Gozzo, Fabio C.; Carvalho, Paulo C. (Elsevier B.V., 2015)
Chemical cross-linking has emerged as a powerful approach for the structural characterization of proteins and protein complexes. However, the correct identification of covalently linked (cross-linked or XL) peptides analyzed by tandem mass spectrometry is still an open challenge. Here we present SIM-XL, a software tool that can analyze data generated through commonly used cross-linkers (e.g., BS3/DSS). Our software introduces a new paradigm for search-space reduction, which ultimately accounts for its increase in speed and sensitivity. Moreover, our search engine is the first to capitalize on reporter ions for selecting tandem mass spectra derived from cross-linked peptides. It also makes available a 2D interaction map and a spectrum-annotation tool unmatched by any of its kind. We show SIM-XL to be more sensitive and faster than a competing tool when analyzing a data set obtained from the human HSP90. The software is freely available for academic use at http://pattemlabforproteomics.org/sim-xl. A video demonstrating the tool is available at http://pattemlabforproteomics.orWsim-xl/video. SIM-XL is the first tool to support XL data in the mzIdentML format; all data are thus available from the ProteomeXchange consortium (identifier PXD001677). This article is part of a Special Issue entitled: Computational Proteomics. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cross-linked; Cross-linking; Protein-protein